1983
DOI: 10.3382/ps.0621028
|View full text |Cite
|
Sign up to set email alerts
|

Choline Supplementation in the Diets of Aged White Leghorn Hens Grouped According to Body Weight

Abstract: A randomized block design experiment was conducted to determine if aged layers require supplemental choline when fed practical corn-soy diets adequate in methionine. Hisex hens (50 weeks old) were divided into four body weight groups containing 120 hens each. Six experimental treatments were prepared by addition of choline to a corn-soy basal diet at 0, 55, 110, 220, 440, and 880 mg/kg of diet. Each diet was fed to four replicates of 5 hens each within each body weight group. The nutrient content in the basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The reduction of fat with the choline supplementation was found by Ruiz et al (1983), who reported that the liver lipid content was significantly higher in extra heavy birds fed the basal diet with no supplemental choline when compared with the average liver lipid content of extra heavy birds fed diets supplemented with choline.…”
Section: Betaine and Choline Administered In Ovomentioning
confidence: 86%
See 1 more Smart Citation
“…The reduction of fat with the choline supplementation was found by Ruiz et al (1983), who reported that the liver lipid content was significantly higher in extra heavy birds fed the basal diet with no supplemental choline when compared with the average liver lipid content of extra heavy birds fed diets supplemented with choline.…”
Section: Betaine and Choline Administered In Ovomentioning
confidence: 86%
“…The dietary requirement for choline in young chickens and turkey poults as a growth promoter was demonstrated by several authors (reviewed in Ruiz et al, 1983). Conversely, in a study conducted by Blair et al (1986) has been observed that choline supplementation did not increase weight gain or feed efficiency for pullets from 8 to 20 weeks of age.…”
Section: Betaine and Choline Administered In Ovomentioning
confidence: 97%
“…Moreover, Gous and Cherry (2004) reported that the light hens reached sexual maturity after the heavy hens. Hens with lighter LBW produce lighter eggs, intake less feed per day, and more efficiently to convert feed to egg mass in comparison with heavier hens (Ruiz et al, 1983 andSummers andLeeson, 1983). However, Nofal and Hassan (2004) found that, Mamourah and Gimmizah large hens showed significantly lower production than that of the medium and small hens.…”
Section: Resultsmentioning
confidence: 99%
“…Body weight at onset of egg production and throughout the production year in uences the e ciency of egg production. Birds with lighter body weights produce lighter eggs [24], consume less feed per day, and convert feed to egg mass more e ciently [24,25] in comparison with heavier birds. With the South African White Leghorns it was found that the optimum body weight at sexual maturity for egg production seems to range between 1•59 to 1•82 kg.…”
Section: Body Weight and Body Weight Of Bovans Brown Layersmentioning
confidence: 99%